Revised Reference Broth Microdilution Method for Testing Telavancin: Effect on MIC Results and Correlation with Other Testing Methodologies - Farrell, David J. (American Society for Microbiology, 2014)
The reference broth microdilution (BMD) antimicrobial susceptibility testing method for telavancin was revised to include dimethyl sulfoxide (DMSO) as a solvent and diluent for frozen-form panel preparation, following the CLSI recommendations for water-insoluble agents. Polysorbate 80 (P-80) was also added to the test medium to minimize proven drug losses associated with binding to plastic surfaces. Four hundred sixty-two Gram-positive isolates, including a challenge set of organisms with reduced susceptibilities to comparator agents, were selected and tested using the revised method for telavancin, and the MIC results were compared with those tested by the previously established method and several Sensititre dry-form BMD panel formulations. The revised method provided MIC results 2- to 8-fold lower than the previous method when tested against staphylococci and enterococci, resulting in MIC(50) values of 0.03 to 0.06 μg/ml for staphylococci and 0.03 and 0.12 μg/ml for Enterococcus faecium and Enterococcus faecalis, respectively. Less-significant MIC decreases (1 to 2 log(2) dilution steps) were observed when testing streptococci in broth supplemented with blood, which showed similar MIC(50) values for both methods. However, Streptococcus pneumoniae had MIC(50) results of 0.008 and 0.03 μg/ml when tested by the revised and previous methods, respectively. Highest essential agreement rates (≥94.0%) were noted for one candidate dry-form panel formulation compared to the revised test. The revised BMD method provides lower MIC results for telavancin, especially when tested against staphylococci and enterococci. This is secondary to the use of DMSO for panel production and the presence of P-80, which ensure the proper telavancin testing concentration and result in a more accurate MIC determination. Moreover, earlier studies where the previous method was applied underestimated the in vitro drug potency.